High and Volatile Treasury Yields in Tanzania : The Role of Strategic Bidding and Auction Microstructure - Sobolev, Yuri.; Abbas, S. M. Ali. (Washington, D.C. : International Monetary Fund, 2008)
The observed increase in the level and volatility of Tanzania's Treasury yields in recent years against an otherwise benign macroeconomic backdrop presented a puzzle for policymakers, while raising concerns about the fiscal burden of rising debt interest payments and diversion of bank credit away from the private sector. Using evidence from bid-level data and supported by theoretical models, this paper argues that oligopolistic bidding through 2005 may have been partly responsible for the rising level of yields; while the high volatility during 2006-07 could be traced to the emergence of a sharp segmentation of the T-bill market between sophisticated financial market players (foreign-controlled banks) and a lessexperienced group of investors (domestic pension funds and small banks). An important policy recommendation that emerges is that public debt managers should avoid micromanaging Treasury bill auctions by issuing amounts in excess of those offered or by dipping into oversubscribed segments of the yield curve, as such practices seriously disadvantage the less-sophisticated (but more competitive) investors vis-a-vis the more sophisticated players.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet